Highly substituted calcium silicates 3D printed with complex architectures to produce stiff, strong and bioactive scaffolds for bone regeneration. (December 2021) - Mirkhalaf, Mohammad; Goldsmith, James; Ren, Jiongyu; Dao, Aiken; Newman, Peter; Schindeler, Aaron; Woodruff, Maria Ann; Dunstan, Colin R.; Zreiqat, Hala
Highlights: We developed 13 new bioceramic compositions by doping mg and Fe into baghdadite. Mg-Baghdadite showed simultaneously improved bioactivity and mechanical properties compared to baghdadite. 3D printed Mg-Baghdadite scaffolds were 2–5 × stiffer and stronger than other ceramic scaffolds printed using photopolymerization. The significant in vivo bone formation in Mg-Baghdadite scaffolds turned them into tough and deformable materials. Abstract: Bone's outstanding biomechanical performance is derived from cooperative interactions between its composition and microarchitecture. Towards developing bioceramic scaffolds with similar biomechanical performance for repairing large bone defects under load, we have developed 13 new bioceramic compositions by doping various concentrations of iron and magnesium into Baghdadite (a Zr-Ca-Silicate: Ca3 ZrSi2 O9 ). The resulting bioceramics were printed into scaffolds with precisely controlled internal and external shapes using a versatile photopolymerization-based stereolithography technique. The biomechanical performance of new compositions and scaffolds were determined using mechanical tests with in situ imaging, in vitro cell study, an in vivo animal study, histological analysis, and microcomputed tomography. Mg-doped Baghdadite with composition Ca3 Mg0.1 Zr0.9 Si2 O8.9 demonstrated superior bioactivity and mechanical properties, compared to Baghdadite. 3D printed Mg-doped Baghdadite scaffolds with 35% porosity and designed architecture matched the stiffness and strength of cortical bone. These scaffolds were 2–5 times stronger than other bioceramic and bioglass scaffolds with the same porosity made with photopolymerization techniques. In vivo bone ingrowth was 2.2 times higher in Mg-doped Baghdadite than Baghdadite, effectively transforming these mechanically brittle scaffolds into deformable and tough ceramic-bone composites. Mg-doped Baghdadite scaffolds demonstrate a combination of favorable mechanical properties and bone regeneration capacity that show their potential for clinical success. Graphical abstract: Image, graphical abstract